Fabrication of pulverized cellulosics by ultra high-pressure water jet treatment and usage in polymer nanocomposites and graft copolymerization - Yoshioka, M.(Kyoto Univ. (Japan)); Sakaguchi, K; Ohno, T; Nishio, Y; Shiraishi, N (Journal of wood science, 2009)
Cellulose powders were pulverized by an ultra high-pressure counter-collision treatment in an aqueous suspension state, and then used in composites with vinyl polymers and graft copolymerized with methyl methacrylate using ceric ion initiator. The influence of freeze-drying methods after microfibrillation of cellulose was visualized by scanning electron microscopy (SEM). The coalescence of microfibrillar structures was observed to increase easily reflecting the freeze-drying conditions. While the degree of microfibrillation was unsatisfactory for use as fillers in preparing polymer-nanocellulose composites, the situation was found to be rectified with the use of a proper kneading technique. The roles of microfibrillated cellulose in processes producing bio-nano-composites suitable for practical uses were studied through SEM observations and measurements of physical properties. The characteristics of the successive graft copolymerization were studied through examining the monomer conversion and the grafting efficiency. The significant improvement in the grafting became apparent in response to the counter-collision pretreatment. Dynamic viscoelastic properties of the molded sheets of the grafted products were studied to measure the effects of the graft copolymerization compared with the corresponding physically blended material and neat poly(methyl methacrylate). The grafting reaction resulted in composites with much higher heat-resisting properties than those obtained for the latter two.